Fruit, vegetable, and fiber intake in relation to cancer risk: findings from the European Prospective Investigation into Cancer and Nutrition (EPIC). - Bradbury, K; Appleby, P; Key, T (American Society for Nutrition, 2014)
Fruit, vegetables, and certain components of plant foods, such as fiber, have long been thought to protect against cancer. The European Prospective Investigation into Cancer and Nutrition (EPIC) is a prospective cohort that includes >500,000 participants from 10 European countries and has made a substantial contribution to knowledge in this research area. The purpose of this article is to summarize the findings published thus far from the EPIC study on the associations between fruit, vegetable, or fiber consumption and the risk of cancer at 14 different sites. The risk of cancers of the upper gastrointestinal tract was inversely associated with fruit intake but was not associated with vegetable intake. The risk of colorectal cancer was inversely associated with intakes of total fruit and vegetables and total fiber, and the risk of liver cancer was also inversely associated with the intake of total fiber. The risk of cancer of the lung was inversely associated with fruit intake but was not associated with vegetable intake; this association with fruit intake was restricted to smokers and might be influenced by residual confounding due to smoking. There was a borderline inverse association of fiber intake with breast cancer risk. For the other 9 cancer sites studied (stomach, biliary tract, pancreas, cervix, endometrium, prostate, kidney, bladder, and lymphoma) there were no reported significant associations of risk with intakes of total fruit, vegetables, or fiber.